Urgensi Kompetensi Penilaian dan Pengambilan Keputusan Bagi Guru - Edy anas Ahmadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The main competence required by teachers is the competence of assessment and decision making (judgment and decision making), which is defined as the ability to draw conclusions about the situation at hand and the ability to make decisions under any conditions, including when under pressure. This ability must be possessed by every individual including the teacher because the condition under pressure or often called stress has become an inseparable part of life. Stress can make someone who experiences it think and try hard in solving a problem or challenge in life as a form of adaptation response to stay afloat. But it also becomes a big problem for teachers because it can affect health and achievement and can have adverse effects on their students